DNA-binding studies of valrubicin as a chemotherapy drug using spectroscopy and electrochemical techniques - Hajian, R.; Hossaini, P.; Mehrayin, Z.; Woi, P.M.; Shams, N. (Elsevier, 2017)
In this study, the molecular interactions between valrubicin, an anticancer drug, and fish sperm DNA have been studied in phosphate buffer solution (pH 7.4) using UV–Vis spectrophotometry and cyclic voltammetry techniques. Valrubicin intercalated into double stranded DNA under a weak displacement reaction with methylene blue (MB) molecule in a competitive reaction. The binding constant (kb) of valrubicin-DNA was determined as 1.75×103 L/mol by spectrophotometric titration. The value of non-electrostatic binding constant (kt 0) was almost constant at different ionic strengths while the ratio of kt 0/kb increased from 4.51% to 23.77%. These results indicate that valrubicin binds to ds-DNA via electrostatic and intercalation modes. Thermodynamic parameters including ΔH0, ΔS0 and ΔG0 for valrubicin-DNA interaction were determined as −25.21×103 kJ/mol, 1.55×102 kJ/mol K and −22.03 kJ/mol, respectively. Cyclic voltammetry study shows a pair of redox peaks for valrubicin at 0.45 V and 0.36 V (vs. Ag/AgCl). The peak currents decreased and peak positions shifted to positive direction in the presence of DNA, showing intercalation mechanism due to the variation in formal potential.